Editorial notes - Ahmad, Khaliq (World Academy of Islamic Management, 2025)
This is an editorial notes written by me as the editor in chief of the Journal of Islamic Management Studies(JIMS). This journal is published by WAIM (World Academy of Islamic Management) bi annually.